EVORA WORKSHOP PROGRESSES DISCUSSIONS ON THE DEVELOPMENT OF REMP FOR THE NORTHERN MID-ATLANTIC RIDGE - Madureira, Pedro (2020)
International experts from member States, including developing counties and sponsoring States as well as from the scientific community, and contractors convened at a workshop held to discuss the development of a Regional Environmental Management Plan (REMP) for the Area of the Northern Mid-Atlantic Ridge in Évora, Portugal, from 25 to 29 November Organized by the International Seabed Authority (ISA), in collaboration with the Government of Portugal and the European Commission through its Atlantic REMP project, the workshop held at the University of Évora in Portugal provided an opportunity for participants to review available scientific information and consider environmental requirements for applying area-based management tools and addressing cumulative impacts from future exploitation activities at a regional scale. To date, ISA has issued three contracts for exploration for polymetallic sulphide deposits in the Area of the Northern Mid-Atlantic Ridge, which are rich in metals such as copper, zinc, lead, gold and silver. Once developed, the aim of the REMP will be to ensure effective environmental protection of this area as required by article 145 of the UN Convention on the Law of the Sea (UNCLOS).